Obtención de un inóculo fúngico para la degradación de un colorante azo por fermentación en estado sólido (2014)
The textile and food industry generate effluents with large amounts of azo dyes, leading to a general detriment of the ecosystem due to the decrease of the photosynthetic process and the available oxygen to aquatic biota. The dyes adsorption over an agro-industrial waste, followed by a degradation process under Solid State Fermentation (SSF) conditions with white-rot fungi is highlighted for the treatment of those pollutants. The aim of this research was to evaluate the fungal inoculum obtained from different culture media and its effect on the degradation percentage of the red dye 40 under SSF conditions. Liquid malt extract medium and PDA solid medium and wheat bran were the different culture media evaluated. The assays were performed using the fungal species Pleurotus ostreatus and Trametes versicolor; the degradation process was monitored for 20 days and then the degradation percentage was determined. The best dye degradation percentage was 93.19% by T. versicolor and 63.15% by P. ostreatus, percentages reached with the obtained fungal inoculum from wheat bran medium and supplemented with malt extract. The variation in the conditions of inoculum growth had a significant incidence on the efficiency of the biodegradation process.